Changing Toronto : Governing Urban Neoliberalism - Boudreau, Julie-Anne (Book collections on Project MUSE., 2009)
""With an eye for global forces, this panoramic account revolves around a focus on social, spatial, and environmental justice in the city, offering a lively riposte to both dull academicism and theatrical boosterism.""--Kanishka Goonewardena, University of Toronto